2022
DOI: 10.21873/cgp.20331
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Translocation t(5;12)(p13;q14) Leading to Fusion of High-mobility Group AT-hook 2 Gene With Intergenic Sequences From Chromosome Sub-Band 5p13.2 in Benign Myoid Neoplasms of the Breast: A Second Case

Abstract: Background/Aim: Recently, we reported a myoid hamartoma carrying a t(5;12)(p13;q14) karyotypic aberration leading to fusion of the high-mobility group AT-hook 2 (HMGA2) gene with a sequence from chromosome sub-band 5p13.2. We describe here another benign myoid tumor of the breast with identical genetic aberrations. Materials and Methods: A mammary leiomyomatous tumor found in a 45year-old woman was studied using cytogenetics, fluorescence in situ hybridization, RNA sequencing, reverse transcriptionpolymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Using cytogenetics, fluorescence in situ hybridization, RNA sequencing, reverse transcription-polymerase chain reaction, and Sanger sequencing methodologies, we showed that the tumor cells had an identical genetic profile to that found in the previously examined myoid breast hamartoma. We conclude that a chromosome translocation t(5;12)(p13;q14) resulting in fusion of HMGA2 with a sequence from chromosome subband 5p13.2 is recurrent in benign myoid neoplasms of the breast (124).…”
Section: Abstract Chromosomal Translocations In Cancer As Well As Ben...mentioning
confidence: 84%
See 1 more Smart Citation
“…Using cytogenetics, fluorescence in situ hybridization, RNA sequencing, reverse transcription-polymerase chain reaction, and Sanger sequencing methodologies, we showed that the tumor cells had an identical genetic profile to that found in the previously examined myoid breast hamartoma. We conclude that a chromosome translocation t(5;12)(p13;q14) resulting in fusion of HMGA2 with a sequence from chromosome subband 5p13.2 is recurrent in benign myoid neoplasms of the breast (124).…”
Section: Abstract Chromosomal Translocations In Cancer As Well As Ben...mentioning
confidence: 84%
“…The data indicated that myoid hamartoma is a true neoplasm growing from a mutated mesenchymal stem cell capable of differentiating into smooth muscle cells (123). In 2022, we reported the genetic characterization of a mammary leiomyomatous tumor without signs of malignancy (124). Using cytogenetics, fluorescence in situ hybridization, RNA sequencing, reverse transcription-polymerase chain reaction, and Sanger sequencing methodologies, we showed that the tumor cells had an identical genetic profile to that found in the previously examined myoid breast hamartoma.…”
Section: Abstract Chromosomal Translocations In Cancer As Well As Ben...mentioning
confidence: 99%
“…FISH analysis was performed on metaphase plates using an inhouse prepared HMGA2 break-apart probe as previously described (20)(21)(22). The centromeric (proximal) part of the probe (red signal) was constructed from a pool of clones RP11-185K16, RP11-30I11, and RP11-662G15.…”
Section: G-banding Karyotyping and Fluorescence In Situ Hybridization...mentioning
confidence: 99%
“…The centromeric (proximal) part of the probe (red signal) was constructed from a pool of clones RP11-185K16, RP11-30I11, and RP11-662G15. The telomeric (distal) part of the probe (green signal) was constructed from a pool of the clones RP118B13, RP11-745O10, and RP11-263A04 (20)(21)(22).…”
Section: G-banding Karyotyping and Fluorescence In Situ Hybridization...mentioning
confidence: 99%
See 1 more Smart Citation